Online teaching in China during the COVID-19 pandemic - Li Yuebo; Siti Hajar Halili; Rafiza Abdul Razak (Institute of Advanced Engineering and Science, 2022)
This study was undertaken to understand the overall impact of China's online education practices at all levels during the COVID-19 pandemic. A study of remote learning was an opportunity to better understand the long-term impact and adoption of structural and pedagogical practices in the post- pandemic period. The main research subjects were teachers and administrators in K-12 primary, vocational colleges and universities. The adult learning andragogy model was utilized as a framework for understanding the conditions under which students and faculty learned and taught in a remote learning environment. Statistical analysis of survey data indicated the research subjects had expectations for a change in teaching methods into the future. Future research is needed to carry out an in-depth analysis of how to build a model for online education. As a result of this study, it was determined that the continuous evaluation of online education would help in shaping best practice for teaching and learning in a remote environment within China’s educational system.